Significance of ipsilateral breast tumor recurrence after breast conserving treatment: role of surgical removal - Demicheli, Romano (AME Publishing Company, 2013)
OBJECTIVE: To analyze the pattern over time (dynamics) of further recurrence and death after ipsilateral breast tumor recurrence (IBTR) in breast cancer patients undergoing breast conserving treatment (BCT). METHODS: A total of 338 evaluable patients experiencing IBTR were extracted from a database of 3,293 patients undergoing BCT. The hazard rates for recurrence and mortality throughout 10 years of follow-up after IBTR were assessed and were compared to the analogous estimates associated to the primary treatment. RESULTS: In a time frame with the time origin at the surgical treatment for IBTR, the hazard rate for further recurrence displays a bimodal pattern (peaks at the second and at the sixth year). Patients receiving mastectomy for IBTR reveal recurrence and mortality dynamics similar to that of node positive (N+) patients receiving mastectomy as primary surgery, apart from the first two-three years, when IBTR patients do worse. If the patients with time to IBTR longer than 2.5 years are considered, differences disappear. CONCLUSIONS: The recurrence and mortality dynamics following IBTR surgical removal is similar to the corresponding dynamics following primary tumor removal. In particular, patients with time to IBTR in excess of 2.5 years behave like N+ patients following primary tumor removal. Findings may be suitably explained by assuming that the surgical manoeuvre required by IBTR treatment is able to activate a sudden growing phase for tumor foci most of which, as suggested by the systemic model of breast cancer, would have reached the clinical level according to their own dynamics.